Segurança em uma célula robotizada - Chia, Ian Mauro Concha (2014)
This work presents a study regarding safety requirements in a robotic work cell applied in an assembling operation in an assembly line, introducing robot setup, main applicable safety devices, monitoring devices and concepts of safety industrial networks. It is proposed a safety category level and safety devices in order to comply with NR12, using Safety PLCs as safety monitoring device of safety sensors and equipments.